2022
DOI: 10.7150/ijms.75824
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effect of obesity and cognitive function decline on the risk of chronic kidney disease progression in patients with type 2 diabetes mellitus: a 9.1-year cohort study

Abstract: Background: Obesity and cognitive function decline are independent risk factors for chronic kidney disease (CKD). However, few studies have examined the combined effects of obesity status and cognitive function on change in CKD risk. We aimed to evaluate the association between obesity status, cognitive function and CKD risk change in patients with type 2 diabetes mellitus (T2DM). Methods: Data on 3399 T2DM patients were extracted from a diabetes disease management program be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Other studies analyzed the relationship between CD, DM-2, and CKD. Thus, a study carried out on 3399 patients with DM-2 showed that obesity and CD are independent risk factors for the progression of CKD, especially in women [ 62 ]. Otherwise, another study determined that patients with DM-2 and CKD, especially those with advanced kidney damage, may have cognitive disorders [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies analyzed the relationship between CD, DM-2, and CKD. Thus, a study carried out on 3399 patients with DM-2 showed that obesity and CD are independent risk factors for the progression of CKD, especially in women [ 62 ]. Otherwise, another study determined that patients with DM-2 and CKD, especially those with advanced kidney damage, may have cognitive disorders [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Domestic and international studies on the relationship between cognitive dysfunction and CKD are currently in the exploratory stage, and there is still debate about the causal relationship between CKD and cognitive dysfunction. Some studies indicate that CKD may cause cognitive dysfunction [9][10][11] , while others imply that cognitive dysfunction may be caused by other factors such as age, education level, vascular disease [12] , hypertension [13] , and diabetes mellitus [14,15] . However, previous studies have revealed limitations, including insu cient statistical robustness and some shortcomings in making causal inferences due to small population sizes, different interpretations of the ndings, and the presence of confounders such as socio-cultural demographic characteristics and pre-existing cerebrovascular events.…”
Section: Introductionmentioning
confidence: 99%